PENGARUH KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO TRANSCOM GUNUNGSITOLI - Laia, Otanius; Waruwu, Suka’aro; Laia, Almed Jaya; Bu’ulolo, Nanny Artatina (Jurnal Suluh Pendidikan, 2025)
This study aims to analyze the influence of service quality and location on purchasing decisions at the Transcom Gunungsitoli Store. The main focus of this study is to determine the extent to which the quality of service provided by the Transcom Store and location factors influence consumer decisions in making purchases. This study uses a quantitative method with data collection through questionnaires distributed to consumers of the Transcom Store. Based on the results of the analysis, it was found that service quality and location significantly influence purchasing decisions. The test results show that the significance value <0.05, which means that these two variables have a real influence on consumer purchasing decisions. In addition, service quality and location contribute 54.9% in influencing purchasing decisions at the Transcom Gunungsitoli Store. These findings indicate that improving service quality and strategic location placement can encourage consumers to make purchases at the Transcom Store.